The relationship between daytime napping and glycemic control in people with type 2 diabetes - Yuan, Jinjin; Wang, Jinle; Chen, Yingdan; Zhang, Min; Zhao, Aimei; Du, Jing; Zhang, Jiahui; Liu, Fan; Wang, Yueying; Chen, Pei; Zhu, Bingqian (Frontiers in Endocrinology, 2024)
Aim: To examine the association between napping characteristics and glycemic control in people with type 2 diabetes.Design: This study used a cross-sectional design.A convenience sample of people with type 2 diabetes (N=226) were included. Glycemic control was indicated by HbA1c which was measured by A1C Now®+. Napping characteristics including napping frequency, duration, timing, and type were measured by validated questionnaires. Other variables, such as insomnia, cognitive impairment, and depression were measured by the Insomnia Severity Index, Montreal Cognitive Assessment, and Patient Health Questionnaire-9, respectively. Multivariate linear regression analyses were performed.The sample consisted of 122 women (54.0%), with a median age of 67 years.Their median HbA1c was 6.8%. No significant relationship was found between napping frequency and HbA1c. Among nappers, after controlling for covariates, long napping duration (≥60 min) and morning napping were both associated with poorer glycemic control. Compared with appetitive napping, restorative napping was associated with better glycemic control.Conclusions: Daytime napping (e.g., duration and type) is an important modifiable factor for glycemic control in people with type 2 diabetes. This study provides new insights into the relationship between napping and glucose management among people with diabetes.